2004
DOI: 10.1007/s00125-003-1260-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and renal sodium handling in three ethnic groups living in England

Abstract: Aim/hypothesis. Increased proximal renal sodium reabsorption is associated with central adiposity and insulin resistance in white men. Our study examined whether this association also exists in other ethnic groups with different prevalences of insulin resistance and associated metabolic abnormalities. Methods. We studied the association between fractional renal excretion of endogenous lithium (FELi) and metabolic syndrome in a population study of 1190 randomly selected men and women who where 40 to 59 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 40 publications
3
13
1
Order By: Relevance
“…Thus, our findings suggest that in subjects with MS a greater avidity of the renal proximal tubule for sodium is compensated for by relative hyperfiltration, which is sustained, at least in part, by higher systemic blood pressure. These findings are in accordance with the results of a recent study on a sample of a Caucasian population in England [7]. They are also in keeping with previous demonstrations of an altered modulation of FPRNa in relation to salt sensitivity in both normotensive [4] and hypertensive individuals [5].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, our findings suggest that in subjects with MS a greater avidity of the renal proximal tubule for sodium is compensated for by relative hyperfiltration, which is sustained, at least in part, by higher systemic blood pressure. These findings are in accordance with the results of a recent study on a sample of a Caucasian population in England [7]. They are also in keeping with previous demonstrations of an altered modulation of FPRNa in relation to salt sensitivity in both normotensive [4] and hypertensive individuals [5].…”
Section: Discussionsupporting
confidence: 94%
“…These findings indicate that essential hypertensive patients with metabolic syndrome, whose sodium sensitivity of blood pressure was elevated, were likely to manifest as non-dippers under a high-sodium diet, and their nocturnal blood pressure fall was restored by sodium restriction. On the other hand, in white men and women, the fractional excretion rates of lithium were inversely associated with a higher waist circumstance and the HOMA index [22], but no associations were found in people of either African or South Asian origin. These results indicated differences in the association between metabolic syndrome and salt sensitivity of the blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…We also decided to study wellcontrolled type 2 diabetes subjects who were, as far as we could judge, clinically free from complications or any comorbidity or treatment. Studies have shown that abnormalities of tubular sodium handling occur even in subjects with the metabolic syndrome (2) and certainly in uncomplicated type 2 diabetes (30). Subjects were studied under fasting conditions with blood glucose levels below the renal threshold to avoid the need for insulin clamping, which would have introduced further variables.…”
Section: Discussionmentioning
confidence: 99%